Selection of Materials and Interrelation of Operating Parameters of Friction Pairs of a New Type of Disc-Shoe Brake of a Drilling Winch - Janahmadov, A.Kh.; Volchenko, D.A.; Javadov, M.Ya.; Volchenko, N.A.; Voznyi, A.V.; Zhuravlev, D.Yu. (Herald of Azerbaijan Engineering Academy, 2025)
Experimental design developments and theoretical studies of disk (tubular type) - shoe brakes of drilling drawworks with forced air cooling of their friction pairs made it possible to establish the following: a method for selecting materials for friction pairs based on their dynamic and thermal energy loading was proposed; the average radius of the disk friction belt and their mutual overlap coefficient were introduced to the known design parameters of friction pairs; the influence of the design parameters of a serial disk brake on the weight of the drill pipe string lowered into the well and its operating parameters, from which the braking torque was extracted; the influence of constant and variable design and operating parameters on the braking torque and a comparison of its value for different cases.